Manfaat Homeopathy Bagi Pertahanan Tubuh Sapi Perah - I Wayan Teguh Wibawan; Agatha Winny Kurniatanti Sanjaya; Yusnani - (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2009)
The effectiveness of homeopathy combination in eliciting nonspecific cellular defense mechanism indairy cows is demonstrated in this study. Two groups of 2-7 years old, in 3-5 months term of pregnancydairy cows which suffering clinical mastitis were used id this study. At 3 weeks and 4 weeks prae partusanimals received their first homeopathy treatment, i.e. Group I: Coenzyme comp®, and Group II: a combinationof Mucosa comp® and Traumeel®, respectively. At one week and two weeks post partus all animals in thetwo groups received their second treatment, i.e. a combination of Lachesis comp® and Traumeel®.Subsequently, at 3 and 4 weeks post partus all animals in the two groups received their third treatment,i.e. a combination of Carduus comp® and Coenzyme comp®, respectively. All homeopathy solutions weregiven at 5 ml subcutaneously. Ten ml of blood samples for haptoglobin analysis were drawn from eachanimal and blood smears for White-Blood-Cell counting and differentiation and phagocytosis activity andcapacity observation were prepared from each animal at 3 and 4 weeks prae partus; and at one week, 3, 5,and 7 weeks post partus, respectively. Our results indicated that although there were non significantdifference in the phagocytosis activity and capacity between animals in Group I and Group II; animals inGroup II showed a marked increase in phagocytosis activity and capacity. Based on haptoglobin analysis,animals in Group II showed a steadily low haptoglobin level in the blood (0.08 mg/ml) up to 3 weeks postpartus and a tendency to further decline until the end of the observation. Based on the WBC counts anddifferentiation, animals in Group II also showed a better response compared to animals in Group I.In conclusion, the use of homeopathy combination is capable in eliciting nonspecific cellular defensemechanism; this phenomena were clearly shown in the combination of Mucosa comp® and Traumeel®. Theuse of this homeopathy combination should be considered at prae partus allowing the recognition of thehost defense mechanism.